The effect of group size and reward on creativity among grade six pupils of Miag-ao Central Elementary School. - Lelis, Jera Mae P.
The study was conducted to determine the effect of group size and reward of creativity among children. sixty grade six pupils of Miag-ao Central Elementary School participated in the study and they were randomly assigned into six experimental conditions namely: Group 1 (3-members without reward), Group 2 (5-members without reward), Group 3 (7-members withou reward), Group 4 (3-members with reward), Group 5 (5-members with reward), and Group 6 (7-members with reward). The Minnesota Circles Task Test was utilized in the study. The circle task test is composed of 30 circles. It is used as a drawing sheet for the participants. It measures the creativity through flexibility, originality, fluency, and elaboration scores., With an(a)=0.05, F critical, df's (1,6)=5.99 result showed that Group size has no significant effect on creativity among children at F computed=0.05. On the other hand, with an alpha (a)=0.05, the F critical at dfs (2,6)=5.14. The F computed=8.21 for reward showed that null hypothesis is rejected. Thus, reward has a significant effect on the creativity among children. Results also revealed that there is no significant interaction effect between group size and reward at F computed=0.05. Therefore, group size and reward act separately on the participants' creativity output.